Theoretical and Methodological Aspects of Organization’s Competitive Strategy Formation - Tarasova, Tatiana Fedorovna; Snitko, Lyudmila Tarasovna; Matuzenko, Elena Viktorovna; Meshechkina, Raisa Petrovna; Voishscheva, Olga Stanislavovna (International Journal of Economics and Financial Issues, 2016)
The article examines the main theoretical and methodical approaches to the organization’s competitive strategy development. It is noted that comprehensive improvement of the competitiveness level, first of all, on the basis of the creation and development of sustainable competitive advantages is the most urgent for domestic organizations. The catalyzer of such a process is the formation of own competitive strategy as a conscious selection of the ways to achieve advantages under the conditions of competitive environment. Such a problem is especially urgent for domestic organizations, which operate in retail, as insufficient level of competitiveness is a considerable obstacle in the improvement of the activity efficiency. On the basis of the critical analysis of different theoretical concepts we have classified organization’s competitive strategies and revealed that organization’s competitive strategy development should be implemented on the basis of organization’s key strategy. We have also identified organization’s competitive strategy development principles, which determine the intensity of competition and the formation of the competitive climate. We have defined the necessity of substantiating the concept and developing the technique of organization’s competitive strategy formation in order to improve the efficiency of functioning of domestic organizations in the competitive environment, which, in its turn, would promote growth of the national economy potential in general. Keywords: competitive strategy, competitive advantage, competitive environment, competitive climate. JEL Classifications: L20, L22, D23, M12